Give me strong moments and time: Combining GMM and SMM to estimate long-run risk asset pricing models - Joachim Grammig; Eva-Maria Schaub (Goethe University Frankfurt, Center for Financial Studies (CFS), 2014)
The long-run consumption risk (LRR) model is a promising approach to resolve prominent asset pricing puzzles. The simulated method of moments (SMM) provides a natural framework to estimate its deep parameters, but caveats concern model solubility and weak identification. We propose a twostep estimation strategy that combines GMM and SMM, and for which we elicit informative macroeconomic and financial moment matches from the LRR model structure. In particular, we exploit the persistent serial correlation of consumption and dividend growth and the equilibrium conditions for market return and risk-free rate, as well as the model-implied predictability of the risk-free rate. We match analytical moments when possible and simulated moments when necessary and determine the crucial factors required for both identification and reasonable estimation precision. A simulation study - the first in the context of long-run risk modeling - delineates the pitfalls associated with SMM estimation of a non-linear dynamic asset pricing model. Our study provides a blueprint for successful estimation of the LRR model.
Keywords: C58; G10; G12; 330; asset pricing; long-run risk; simulated method of moments